Video In Situ Snowfall Sensor (VISSS) data for Eriswil on 2024-02-09 - Maahn, Maximilian; Ettrichrätz, Veronika (In: Maahn, M; Ettrichrätz, V (2025): Video In Situ Snowfall Sensor (VISSS) data for Eriswil (2023-2024) [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.981222, 2025)
The VISSS is a camera system recording precipitating snowfall from two perspectives. Here, movies and images of falling precipitation particles are provided for one day at station Eriswil. For further details on the VISSS see Maahn et al. (2024).
Keywords: eriswil; In-situ experiment; precipitation; snowfall measurements